PENGARUH KONSENTRASI ETANOL TERHADAP KARAKTERISTIK EKSTRAK PEWARNA ALAMI BUAH MERAH (Pandanus conoideus Lamk.) DAN APLIKASINYA PADA PRODUK PANGAN - Magdalena Sirwutubun; Maya M. Ludong; Dekie Rawung (Universitas Sam Ratulangi, 2016)
ABSTRACTRed fruit (Pandanus conoideus Lamk) is an endemic plant of Papua that can be developed as one of the food coloring sources of Indonesia. Other than that, red fruit also is a source of natural dyes, because it contains active compounds such as Î±-carotene, Î²-carotene, Î²-kriptosantin, and Î±-tocopherol, and unsaturated fatty acids, especially oleic acid, linoleic and palmitoleic. Red fruit contains carotenoids that produce the orange-red pigment. The purpose of this research is to analyze the effect of concentration of ethanol on the extraction of red fruit as a natural coloring food and also to analyze the level of applying acceptance of this coloring products to the pudding and layer cake. The method is implememted the Complete Random Design (RAL) with differences concentration of ethanol. The results showed that 70% concentration of etanol yield 0,260 of total carotenoids, 2,856 of color intensity, color stability to light ranges from 0.263 to 0.689. The concentration of 60% ethanol yield of total 0,171 carotenoids, 2,693 color intensity and color stability to light ranges from 0,602 to 0,657. Sensory testing of the extraction of red fruit as a natural dyes to the flavor, aroma, and color that preferred by the panelists is treated with 70% concentration of ethanol.